Model Prototype Early Warning System Pada Pemeliharaan Jalur Lengkung Berbasis Mikrokontroler (Politeknik Perkeretaapian Indonesia Madiun, 2022)
The operation of railway infrastructure is regulated in the Government Regulation of the Republic of Indonesia Number 56 of 2009 concerning the Operation of Railways. In order to maintain the reliability of railway infrastructure or facilities, maintenance is necessary. At the time of maintenance of infrastructure on the curved line, the workers received very little information about the trains that would pass through the track being repaired. So a new system is needed to give warnings for passing trains. The new system is prototyped using a proximity sensor-based microcontroller. Information is obtained when the proximity sensor detects the presence of objects in front of it by emitting infrared rays. The proximity sensor is set to detect something less than 80 cm away as input and issue warning information. This prototype is made in 2 modes for single and double lanes, and can be turned off in 1 lane only. Alerts are on a curved path helping workers get information more effectively and efficiently. Thus reducing the risk of accidents. Because when the arch is closed, you can't see the direction of the train's arrival. However, with this system, workers get information in real time.